2016
DOI: 10.5424/sjar/2016143-9053
|View full text |Cite
|
Sign up to set email alerts
|

Is a combination of different natural substances suitable for slug (Arion spp.) control?

Abstract: In a laboratory study we investigated the contact and barrier efficacy of different natural substances (wood ash, sawdust, hydrated lime, and diatomaceous earth) against slugs of the genus Arion, an important agricultural pest. Natural substances were tested individually and in combination with each other. The experiment was carried out in plastic petri dishes and in glass insectaria. Moistened tampons and fresh leaves of lettuce were placed into both experimental arenas. The slugs were starved for 48 hours pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…The recommendation to use this material to kill molluscs, or to deter their feeding on foliage, lacks consistent scientific support. Recently, the lack of diatomaceous earth efficacy also was noted by Laznik and Trdan (2016), although Ciomperlik et al (2013) observed some bioactivity depending on the species of snails evaluated. Even with insects, diatomaceous earth is not always an effective insecticide (Martindale & Newlands 1981).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The recommendation to use this material to kill molluscs, or to deter their feeding on foliage, lacks consistent scientific support. Recently, the lack of diatomaceous earth efficacy also was noted by Laznik and Trdan (2016), although Ciomperlik et al (2013) observed some bioactivity depending on the species of snails evaluated. Even with insects, diatomaceous earth is not always an effective insecticide (Martindale & Newlands 1981).…”
Section: Discussionmentioning
confidence: 93%
“…However, Korunić (1997) noted that the toxicity of diatomaceous earth to insects can vary greatly depending on such factors as pH, shape and size of particles, size distribution, SiO 2 content, adsorption, and whether their origin was freshwater or marine diatoms. Laznik and Trdan (2016) were similarly unable to demonstrate significant toxic effects on molluscs when treated with diatomaceous earth. Silica also occurs naturally in some plants where it can have a major role in defense against insect herbivory (Reynolds et al 2009).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, new molluscicidal substances that are environmentally acceptable have been proposed [22,24,25]. New natural compounds are characterized as selective and highly toxic to target pests, safe for non-target organisms, low cost, and biodegradable [1,25]. The use of wood ash has been noted among these compounds [2,25].…”
Section: Discussionmentioning
confidence: 99%